Pola Asuh Orangtua Dalam Pemberian Makanan Pada Anak yang Mengalami Obesitas - Sumiati Sinaga; Wahyu Dewi Sulistyarini; Indy Putra Nur Pama Rusfan (Jurnal Medika : Karya Ilmiah Kesehatan, 2017)
Overweight or obesity in children is a growing global health problem. One of the highest areas is the province of East Kalimantan. This data shows five of children aged 5-12 years are obese. Obesity is a condition where the body becomes heavier than normal due to the accumulation of excess fat. The cause of obesity itself is multifactorial, both individual factors (biologic and psychological) and environmental factors. The study aims to describe the parenting style of feeding in children who are obese in the working area of ​​West Bontang Health Center. This study uses qualitative research methods with a phenomenological approach. Participants in this study were 7 parents who had obese children. Participant selection uses purposive sampling. This research has 6 main themes, namely feeding children who exceed normal limits at their age, family meal menus that are not good for children's health, the principle of control over eating, the principle of emotional feeding, activities that do not generate much energy, the application of healthy life to control weight excessive body in children. Based on the results of the study it can be concluded that the picture of parenting in feeding shows that the mother is an important role in regulating daily household arrangements including regulating food menus and regulating nutritional status in children. Parents' principle in feeding children who often happens is parents. with groups of parenting emotional feeding because parents do not have the heart to behave with the behavior of children who are somewhat rebellious or angry if their appetite is limited by parents.